Young's Modulus of Single-Crystal Fullerene C𝟕𝟎 Nanotubes - Tokushi Kizuka; Kun'ichi Miyazawa; Takayuki Tokumine (Journal of Nanotechnology)
We performed bending tests on single-crystal nanotubes composed of fullerene C70 molecules by in situ transmission electron microscopy with measurements of loading forces by an optical deflection method. The nanotubes with the outer diameters of 270–470 nm were bent using simple-beam and cantilever-beam loading by the piezomanipulation of silicon nanotips. Young's modulus of the nanotubes increased from 61 GPa to 110 GPa as the outer diameter decreased from 470 nm to 270 nm. Young's modulus was estimated to be 66% of that of single-crystal C60 nanotubes of the same outer diameter.